Television in the Formation of Civil Society: The Role of a Non- Controversial Public Space in Hong Kong - Lee, Paul S. N. (Television, Regulation and Civil Society in Asia, 2002)
Television first appeared in Hong Kong in 1957. It was a cable television service run by the Rediffusion Company which had operated a highly successful wired sound broadcasting service since 1949. Hong Kong was the first British colony to have television. But the Rediffusion television service was very expensive. Its monthly subscription fee was HK$55. In 1958, a technical worker’s monthly wages were HK$360 and an unskilled worker earned only HK$75 (Hong Kong Government 1959: 32). A year before the introduction of free-to-air television in 1967, Rediffusion television had only 67,000 subscribers (Hong Kong Government 1967: 206). Thus before 1967 television was an elite medium and its social impact was minimal.
Num Pages: 8
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Hong Kong (corpus analysé); Hong Kong (lieu de production du savoir); _Nettoyé

Out of Reach: Television, the Public Sphere and Civil Society in the Philippines - Santos, Josefina M. C. (Television, Regulation and Civil Society in Asia, 2002)
In the uprising of 16-20 January 2001, which ousted former Philippine President Joseph Estrada from power, two forces stood out as pivotal: television (specifically the coverage of the impeachment trial which was the centre of public attention) and civil society (which was instrumental in the uprising itself). In this chapter I argue that notwithstanding the central importance of television in this most recent national political change, the regulation of the sector and its long-term associations with crony capitalism have established barriers to civil society finding its voice on television.
Num Pages: 1
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Philippines (corpus analysé); Philippines (lieu de production du savoir); _Nettoyé

India Talking: Politics, Democracy and News Television - Mehta, Nalin (Television in India: Satellites, Politics and Cultural Change, 2008)
After four decades of state monopoly over television Indian viewers gottheir first taste of private television in the early 1990s. By 1998, the first of India’s private 24-hour news channels was on the airwaves and by 2007more than 300 satellite channels were broadcasting into Indian homes. Ofthese, 106 broadcast news in 14 languages and as many as 54 of these were24-hour news channels in 11 languages.1 These are conservative figures thatdo not include many foreign and local cable networks that also broadcastnews.2 Even so, the numbers are a stark illustration of how the Indian statelost control over television broadcasting despite its best efforts to the con-trary. No other country in the world has such a concentration of private news channels as India. The creation of a television public has significantimplications for democracy and this essay focuses on what 24-hour newsmeans for India. It argues that the emergence of television news networkshas greatly enhanced and strengthened deliberative Indian democracy.Commercial mass media stands at the junction of politics and the economy,enabling the entry of citizens onto the stage of politics, while simultaneouslyseeking to appropriate that energy for its own commercial benefit (Rajago-pal, 1999: 133). This is a claim that needs to be differentiated from the usual journalistic self-image of the fourth estate acting as vigilant defenders ofdemocratic ideals. That notion should not be romanticised too muchbecause news production itself is a cultural process that cannot be separatedfrom its social environment. News producers always function under certaininstitutional constraints that are endemic to the news-gathering process.Leftist and liberal scholars of the media differ in their emphasis but allagree that news production is always circumscribed by institutional filters.3News is ‘more a pawn of shared suppositions than the purveyor of selfconscious messages’ (Schudson, 1995: 15). Yet, the media are important,and while it is difficult to draw direct causal linkages, there is no doubt thatthey initiate and create a new sphere of political action.
Num Pages: 30
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Identités diasporiques; Inde (corpus analysé); Singapour (lieu de production du savoir); _Nettoyé

Prime Time Soap Operas on Indian Television - Munshi, Shoma (Routledge India, 2020)
This book examines the phenomenon of prime time soap operas on Indian television. An anthropological insight into social issues and practices of contemporary India through the television, this volume analyzes the production of soaps within India’s cultural fabric. It deconstructs themes and issues surrounding the "everyday" and the "middle class" through the fiction of the "popular". In its second edition, this still remains the only book to examine prime time soap operas on Indian television. Without in any way changing the central arguments of the first edition, it adds an essential introductory chapter tracking the tectonic shifts in the Indian "mediascape" over the past decade – including how the explosion of regional language channels and an era of multiple screens have changed soap viewing forever. Meticulously researched and persuasively argued, the book traces how prime time soaps in India still grab the maximum eyeballs and remain the biggest earners for TV channels. The book will be of interest to students of anthropology and sociology, media and cultural studies, visual culture studies, gender and family studies, and also Asian studies in general. It is also an important resource for media producers, both in content production and television channels, as well as for the general reader.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Inde (corpus analysé); Koweït (lieu de production du savoir); _Nettoyé

Culture, Politics, and Television in Hong Kong - Ma, Eric Kit-wai (Routledge, 1999)
Ma looks at the ways in which the identity of Hong Kong citizens has changed in the 1990s especially since the handover to China in 1997. This is the first analysis which focuses on the role, in this process, of popular media in general and television in particular. The author specifically analyses at the relationship between television ideologies and cultural identities and explores the role of television in the process of identity formation and maintenance.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Hong Kong (corpus analysé); Hong Kong (lieu de production du savoir); _Nettoyé

Television Regulation and Media Policy in China - Chin, Yik-Chan (Routledge, 2016)
Since the late 1990s, there has been a crucial and substantial transformation in China’s television system involving institutional, structural and regulatory changes. Unravelling the implications of these changes is vital for understanding the politics of Chinese media policy-making and regulation, and thus a comprehensive study of this history has never been more essential. This book studies the transformation of the policy and regulation of the Chinese television sector within a national political and economic context from 1996 to the present day. Taking a historical and sociological approach, it engages in the theoretical debates over the nature of the transformation of media in the authoritarian Chinese state; the implications of the ruling party’s political legitimacy and China’s central-local conflicts upon television policy-making and market structure; and the nature of the media modernisation process in a developing country. Its case studies include broadcasting systems in Shanghai and Guangdong, which demonstrate that varied polices and development strategies have been adopted by television stations, reflecting different local circumstances and needs. Arguing that rather than being a homogenous entity, China has demonstrated substantial local diversity and complex interactions between local, national and global media, this book will be of interest to students and scholars of Chinese media, politics and policy, and international communications.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Chine (corpus analysé); Chine (lieu de production du savoir); _Nettoyé

Cultural Polysemy and Vernacular Cosmopolitanism in the Theme Songs of Hong Kong Television Dramas - Kai Khiun, Liew (Television Histories in Asia, 2015)
In 1980, Hong Kong’s commercial Television Broadcast Limited (TVB) television drama The Bund ( 上海滩 ) was popularly received in the city as well as in South-East Asia and the broader Chinese diaspora. Set in the cosmopolitan treaty port of Shanghai in the 1920s, The Bund revolves around the violent ascent of a coolie (Ray Lui) and a disillusioned student activist (Chow Yun-Fat) to become prominent mobsters. Not only were two sequels made within that year, but this historical gangster drama has been repeatedly resurrected in television dramas and fi lms, including Chow’s redux, The Last Tycoon ( 大上海 ), three decades later in 2012. From karaoke lounges to social media sites, theme songs of The Bund remain popular more than three decades after the dramas were screened . With music composed by Joseph Koo, lyrics by Wong Jim and sung by Frances Yip, the main and supplementary theme songs refl ected the intimate role of the Hong Kong-based contemporary Cantonese popular music, or Canto-pop, in cultivating a more memorable and enduring televisual culture. With the smooth synchronization of Koo’s classical music with the undulating pitch of Yip, the song articulates the unpredictable tribulations of the changing fortunes in the treaty-port of Shanghai in the interwar years. To a certain extent, it is also a narrative that reminds viewers in Hong Kong and beyond of similar socio-political and historical predicaments.
Num Pages: 18
Keywords: 1-TV; 2-Analyses formalistes; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Hong Kong (corpus analysé); Singapour (lieu de production du savoir); _Nettoyé

Sange ThakunBangla News Channels and Media-Citizenry - Gupta, Nilanjana (Channeling Cultures: Television Studies from India, 2014)
With special reference to the current scenario in West Bengal, this chapter argues that the rise and popularity of Bangla news channels like Star Ananda, 24 Ghanta, Kolkata TV, and Tara News have resulted in the emergence of a vernacular style of news broadcasting which is quite distinct from that of global or national news media. One major point in this chapter is how the vernacular news channels encourage particular forms of address — the emotional, the intimate and the melodramatic — and how close-ups and sound bites create particular kinds of telegenic political leaders who can use these formal characteristics to their advantage. This chapter explores the ways in which a distinctive kind of vernacular is reconfiguring the nature of political participation itself and hence the notion of citizenship and perhaps even the nature and functioning of the nation-state in India.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Inde (corpus analysé); Inde (lieu de production du savoir); _Nettoyé

When Live News was Too Dangerous: The Early History of Satellite TV in India - Mehta, Nalin (Channeling Cultures: Television Studies from India, 2014)
A unique confluence of technological, political and economic factors in the 1990s drove the transformative process that led to the battering down of the government’s monopoly over television. By the end of the 1990s, the growing strength of Indian capitalism after the liberalization of the Indian economy and the forces of what Thomas Friedman has called ‘Globalisation 3.0’ allowed Indian entrepreneurs to level the playing field. The Indian state, having embarked on economic liberalization, was forced to adapt to satellite television as an agent of global capitalism it certainly did not give up control over television easily or voluntarily. Operating at the junction of public culture, capitalism and globalization, satellite news networks have had profound implications for the state, politics, democracy and identity formation. Despite all their shortcomings and sensationalism, the emergence of satellite television news networks has enhanced and strengthened deliberative Indian democracy.
Keywords: 1-TV; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Inde (corpus analysé); Inde (lieu de production du savoir); _Nettoyé

Television News and an Indian Infotainment Sphere - Thussu, Daya Kishan (Channeling Cultures: Television Studies from India, 2014)
The exponential growth of television news in India – from one state controlled network until 1991 to more than 100 news channels in 2012 – has transformed broadcast journalism in the country. This proliferation of news networks has intensified competition for audience and advertising revenue, leading to excessive marketization of news, which increasingly veers toward infotainment. The chapter examines the challenges faced by Indian television news – focusing on economic and political dimensions of television news - and its implications for the world’s largest democracy.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Hong Kong (lieu de production du savoir); Inde (corpus analysé); _Nettoyé

From Clients to Consumers: The Missing Citizens among the Indian Television Audience - Sinha, Dipankar (Channeling Cultures: Television Studies from India, 2014)
Beneath many instances of ’sweeping’ change, both structural and representational, in the market-dominant, liberalized and privatized Indian televisual scenario there lies a hidden transcript of continuity insofar as the encoding of development issues, images and messages is concerned. In the periods of Doordarshan and later corporate channels, though with markedly different historical contexts, reference points, contents and styles — the encoding of ’development’ leaves little autonomy to the audiences. In a political slant indicating how the two televisual periods converge in contracting the space for public debate and civic engagement the essay seeks to make a departure from the dominant view which puts them in binary positions.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Inde (corpus analysé); Inde (lieu de production du savoir); _Nettoyé

A Local Mode of Programme Adaptation: South Korea in the Global Television Format Business - Lee, Dong-Hoo (Television Across Asia: TV Industries, Programme Formats and Globalisation, 2003)
Television has been called ‘a Western-originated project’ (Barker 1997: 5) and an institution of Western capitalist modernity. The global circulation of Western-centred, or more speciﬁcally, American-centred cultural products, contributes to the formation and dissemination of a global shared culture that reaches across the boundaries of nation-states. In the process American cultural products play a role in the formation of local television cultures.
Num Pages: 18
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Corée du Sud (corpus analysé); Corée du Sud (lieu de production du savoir); _Nettoyé

Feeling Glocal: Japan in the Global Television Format Business - Iwabuchi, Koichi (Television Across Asia: TV Industries, Programme Formats and Globalisation, 2003)
In March 2001 a Japanese newspaper report entitled ‘Indians are addicted to a quiz show’ drew attention to a phenomenally popular television programme in India – a quiz show that attracts millions of viewers in which challengers strive to win prize money (Asahi Shinbun 2001). What was particularly eye-catching for the journalist was the proﬂigately decorated studio set located in Mumbai (Bombay) and the caring guidance of the MC, a ﬁlm star famous in India. The name of the show, as you might have already inferred, was Who Wants To Be A Millionaire?.
Num Pages: 15
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Japon (corpus analysé); Japon (lieu de production du savoir); _Nettoyé

Globalization and Television: A Study of the Indian Experience, 1990-2010 - Narayan, Sunetra Sen (Oxford University Press, 2013)
This study explores the globalization and liberalization that has occurred in Indian television over the two decades starting from 1990.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Inde (corpus analysé); Inde (lieu de production du savoir); _Nettoyé

The Little Emperors’ New Toys: A Critical Inquiry into Children and Television in China - Zhao, Bin (Springer, 2013)
Drawing on original research I conducted in the late 1980s, the book argues for a critical approach to the study of children and television. It begins with critical reappraisals of previous empiricist and interpretative studies to set the ground for a different theoretical inquiry which links biography with history. The situated activity of children's television viewing therefore has to be related to the broader historical and cultural formations in post-Mao China. By way of a methodological pluralism of questionnaire survey, in-depth interviews and observation, the book provides the reader with a thorough critical analysis of the rise of the new commercial ethic in Chinese society in general, and in the sector of media and communications in particular, at the very historical turning point of the late 1980s. Soon after that, Deng Xiaoping made his significant tour to south China, reckoning a big step forward towards further liberalization and started to form a brave new world in China ever since.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Chine (corpus analysé); Chine (lieu de production du savoir); _Nettoyé

Television in Bangladesh: News and Audiences - Roy, Ratan Kumar (Routledge India, 2020)
This book examines the role of 24/7 television news channels in Bangladesh. By using a multi-sited ethnography of television news media, it showcases the socio-political undercurrents of media practices and the everydayness of TV news in Bangladesh. It discusses a wide gamut of issues such as news making; localised public sphere; audience reaction and viewing culture; impact of rumours and fake news; socio-political conditions; protest mobilization; newsroom politics and perspectives from the ground. An important intervention in the subject, this book will be useful to scholars and researchers of media studies, journalism and mass communication, anthropology, cultural studies, political sociology, political science, sociology, South Asian studies, as well as television professionals, journalists, civil society activists, and those interested in the study of Bangladesh.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Bangladesh (corpus analysé); Inde (lieu de production du savoir); _Nettoyé

Film and Television Culture in China - Zhifeng, Hu (Paths International, Limited, 2018)
Film and Television Culture in China gives a provocative analysis of film and television culture in China. The author first gives a panoramic picture of Chinese culture in which film and television was born and shaped. He then delineates the definition, composition, and basic relations in film and television culture. Also discussed are the two traditions in Chinese film and television culture–the worldly spirit and the poetic style. The two traditions are deeply rooted in Chinese Confucianism and Taoism, and have influenced Chinese film and television from the start. The author provides in-depth and original readings of the phenomena in Chinese film and television culture, such as: the reform films and the reflection films; the character and mission of television documentary; and a dialogue between the mainland and Taiwan. Film and Television Culture in China will be an essential guide to understand the film and television culture in China, from early screen to the present day.
Keywords: 1-Cinéma; 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Chine (corpus analysé); Chine (lieu de production du savoir); _Nettoyé

Telly-Guillotined: How Television Changed India - Shah, Amrita (SAGE Publications India Pvt, Ltd., 2019)
Fist-fights in television studios, dwindling media autonomy, sensationalism, fake news, religious hate, abusive trolls, political spin ... How did we get here? Three decades ago, before economic liberalization, came the expansion and privatization of Indian television. Technological innovation and easing of government controls offered the prospect of journalistic independence, artistic creativity and an empowered citizenry. This was rendered illusory by runaway growth and untrammelled commercialization. In that thwarted promise of the late 20th century lie the seeds of Indian democracy's current crisis. Telly-Guillotined: How Television Changed India tells the story of how technology was usurped, first by propagandists, then by the market. Going behind the scenes of the world′s greatest media explosion, this book describes the impact of consumerism on the newsroom, the shaping of a new cultural politics and the rise of a new politics of seduction. In a landscape of technological innovation, blurred boundaries and sensory overload, Amrita Shah paints a picture of the Fourth Estate′s challenging future.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Inde (corpus analysé); Inde (lieu de production du savoir); _Nettoyé

New Television, Globalisation, and the East Asian Cultural Imagination - Keane, Michael; Fung, Anthony Y. H.; Moran, Albert (Hong Kong University Press, 2007)
This volume is divided into three parts: 'Adaptation and Local Production in East Asia', 'Formats, Clones, and Generic Variations' and 'New Television'.
Keywords: 1-TV; 2-Analyses formalistes; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; Australie (lieu de production du savoir); Chine (corpus analysé); Corée du Sud (corpus analysé); Hong Kong (corpus analysé); Hong Kong (lieu de production du savoir); Japon (corpus analysé); Taiwan (corpus analysé); _Nettoyé

From TRT to Netflix: Implications of Convergence for Television Dramas in Turkey - Yanardağoğlu, Eylem; Turhallı, Neval (Television in Turkey: Local Production, Transnational Expansion and Political Aspirations, 2020)
Since the1980s, the television (TV) drama has proved to be one of the most dominant formats on Turkish TV channels and occupied major slots on primetime throughout the 1990s and 2000s. As Internet penetration grew, on-demand services transformed audiences’ expectations of TV series. Internet series first became a trend on YouTube in 2013, and Netflix began broadcasting in Turkey at the beginning of 2016. Its entry to the sector triggered video-on-demand suppliers like Blu TV and Puhu TV which are digital enterprises of Doğan and Doğusṃ Holdings. Blu TV announced their first original project in 2017, Masum (Innocent), which was a big-budget series that included famous actors. In the same year, Puhu TV released their first original, Fi (Phi). Finally, Netflix launched their first original production in Turkey, Hakan: The Protector, in 2018. This chapter focuses on the implications of convergence for the production and distribution of TV dramas and considers the changes in the sector as television broadcasting shifted to new media platforms in Turkey.
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; Turquie (corpus analysé); Turquie (lieu de production du savoir); _Nettoyé

Continuities and Changes in the Transnational Broadcasts of TRT - Karanfil, Gökçen (Television in Turkey: Local Production, Transnational Expansion and Political Aspirations, 2020)
This chapter traces the evolution of the Turkish Public Service Broadcaster with a focus on its transnationalization. Drawing parallels between the changing dynamics in politics, culture, and media in Turkey; contemporary cosmopolitan media cultures; and the continuities and changes in Turkish Radio and Television Corporation’s (henceforth TRT) identity as a public service broadcaster, I shed light on the ways in which TRT has been engaging in transnational broadcasts since the beginning of 1990s. For this I elaborate on the ways in which transnational broadcasting processes in Turkey have been influenced by media transnationalization around the world. I discuss two different incentives behind TRT’s transnational endeavors. First, I elaborate on TRT’s attempts at engaging with the Turkish diaspora around the world; later, I articulate how, in more recent years, TRT sets out to exert a Turkish cultural presence in the Middle East and North Africa (MENA) region. The chapter aims to draw a general portrait of the concept of transnational broadcasting in Turkey with a specific focus on the country’s public service broadcaster, TRT.
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; Turquie (corpus analysé); Turquie (lieu de production du savoir); _Nettoyé

The Regulation of Television Content in Turkey: From State Monopoly to Commercial Broadcasting and Beyond - Sümer, Burcu; Taş, Oğuzhan (Television in Turkey: Local Production, Transnational Expansion and Political Aspirations, 2020)
In contrast with radio broadcasting, which began in 1927, television started remarkably late in Turkey. When the country’s sole public service broadcaster, Turkish Radio and Television Corporation (TRT), was established in 1964 and all of the radio transmitters were transferred to the Corporation, even radio broadcasting was not successfully institutionalized to catch up with its Western counterparts. For a very young Republic like Turkey, radio was an integral part of the modernization and nation-building agenda of the early ruling elite and therefore it institutionalized as a part of the machinery of the state, under very strict state control. Much known indispensable merits of autonomy and independence attributed to the historical public service broadcasting model in Europe were hardly appreciated and supported in Turkey. Television broadcasting also had its share from this negative perception and had to face similar obstructions as radio from the beginning. This chapter traces the history of content regulation in television broadcasting by situating the political controversies at the center at different times from the 1960s until today. Unfortunately, as the saying goes, there is nothing new under the sun, not in Turkey.
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; Turquie (corpus analysé); Turquie (lieu de production du savoir); _Nettoyé

TV China: Control and Expansion - Zhu, Ying (The Routledge Companion to Global Television, 2019)
The chapter traces the evolution of Chinese television since 1958 from a state propaganda organ to a profit-generating media juggernaut, with China Central Television (CCTV) as the only network TV responding to both market principles and party directives. Commercialization and marketization played a major role in the rapid development of the Chinese television industry. In recent years China’s TV industry has witnessed the rise of private media companies and the rapid expansion of digital media and the proliferation of over the top (OTT) content. The chapter further provides an overview of China’s overall TV structures and teases out the relationship between CCTV and local stations. The most popular genre on Chinese TV is serial drama, which developed from predominantly single-episode anthology dramas in the 1980s to chiefly multi-episode serial dramas. Talk shows and reality TV became fashionable since the late 1990s.
Num Pages: 9
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; Chine (corpus analysé); Hong Kong (lieu de production du savoir); _Nettoyé; États-Unis (lieu de production du savoir)

Arab Television Industries: Enduring Players and Emerging Alternatives - Khalil, Joe F. (The Routledge Companion to Global Television, 2019)
This chapter provides an overview and analysis of emerging alternatives in the context of Arab television production, programming, and distribution. Media convergence and the access to digital technologies have accentuated the fragmentation of audiences, revenue streams, and forced alliances and competitions between previously discrete sectors of the media business. Yet, alternative practices are closely associated with changing political, economic, and cultural vectors in the Arab region and the increasing integration of its television industries in global media. The chapter argues that these alternatives constitute a set of continuities with the history of Arab television. Taken together, they also demonstrate some level of transformation in production practices, programming strategies, and distribution operations.
Num Pages: 10
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Qatar (lieu de production du savoir); _Nettoyé

The Social and Political Dimensions of Global Television Formats: Reality Television in Lebanon and Saudi Arabia - Kraidy, Marwan (Global Television Formats: Understanding Television Across Borders, 2012)
When scholars and policy makers contemplate the Arab “media revolution,” they mostly think of Al-Jazeera and its news competitors. They are guided by the assumption that all-news satellite television networks are the predominant, even the single, shaper of the Arab public sphere, a perspective exacerbated by the September 11, 2001 attacks. Drawing on a larger work (Kraidy, 2009, forthcoming), this chapter presents an alternative view, emphasizing instead the combined impact of Arab entertainment television and small media such as mobile phones on Arab governance. It explores how entertainment television is an active contributor to shaping what Arab publics discuss and do in both the social and political realms. As local (in this case regional/pan-Arab, reaching two dozen Arabic-speaking countries) adaptations of global television formats, Arab reality television shows exhibit a combination of signs and practices from several worldviews. As such, this chapter will show how Arab reality shows are open to multiple processes of appropriation and redeployment. Though numerous scholars have for years studied the differentiated “reception” of television texts in various contexts, this chapter focuses speciﬁcally on television formats in a context of growing media convergence and protracted political instability and social upheaval. Speciﬁcally, it focuses on reality television’s social and political impact, which stems primarily from its activation of new communication processes between a variety of information and media technologies creating what I call “hypermedia space.” In the new Arab information order, reality television activates hypermedia space because it promotes participatory practices like voting, campaigning and alliance building, via mobile telephones and related devices.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Arabie Saoudite (corpus analysé); Liban (corpus analysé); Qatar (lieu de production du savoir); _Nettoyé

The International Encyclopedia of Media Studies: Media History and the Foundations of Media Studies - Valdivia, Angharad N.; Nerone, John C.; Mayer, Vicki; Mazzarella, Sharon R.; Parameswaran, Radhika E.; Scharrer, Erica; Darling-Wolf, Fabienne; Gates, Kelly (Wiley-Blackwell, 2013)
Keywords: 1-Cinéma; 1-Jeux vidéo; 1-TV; 2-Analyses formalistes; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma; _À vérifier-Télé

Woke Gaming: Digital Challenges to Social Injustice - Gray, Kishonna L.; Leonard, David J. (University of Washington Press, 2018)
From #Gamergate to the daily experiences of marginalization among gamers, gaming is entangled with mainstream cultures of systematic exploitation and oppression. Whether visible in the persistent color line that shapes the production, dissemination, and legitimization of dominant stereotypes within the industry itself, or in the dehumanizing representations often found within game spaces, many video games perpetuate injustice and mirror the inequities and violence that permeate society as a whole. Drawing from the latest research and from popular games such as World of warcraft and Tomb raider, Woke gaming examines resistance to spaces of violence, discrimination, and microaggressions in gaming culture. The contributors of these essays identify strategies to detox gaming culture and orient players toward progressive ends, illustrating the power and potential of video games to become catalysts for social justice
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé

History First-Hand: Memory, the Player and the Video Game Narrative in the Assassin's Creed Games - Menon, Lakshmi (Rupkatha Journal on Interdisciplinary Studies in Humanities, 2015)
This paper will look at the convergence of the interactive free flow of video games and the questioning and revisioning of historical continuity using the example of the Assassin's Creed series by Ubisoft. With a story that exists simultaneously in the modern day and the 15th century, the games allow the player to take control of characters and alter, or make possible, events recognisable as historical fact. It plays with both history and memory and history as memory, as the life of the primary player character is being relived through the genetic memories of one of his descendants. Being highly narrative-bound, the Assassin's Creed games use, via the medium of the screen, the rift between history and memory as a central element of narrative, theme, and game design, which this paper will explore. Furthermore, using theories of convergence this paper will examine how video games provide a new, interactive mode of storytelling that is rapidly becoming representative of our age.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Digitalizing the Narratives: Structural Analysis of Far Cry 3 - Ali, Eeshan; Karati, Arijit (Rupkatha Journal on Interdisciplinary Studies in Humanities, 2015)
Every form has its own structure. Technically, though there is a difference between computer games and literature, but structurally both reflect same modes of the presentation which is carried out by certain codes. The present paper looks into the structural analysis of computer games with technical aspect as well as literature aspect with special reference to Far Cry 3, a first person action adventure computer game which received several awards and critically acclaimed for its graphics, story line, features etc. Besides this paper relocate Vladimir Propp’s theory of narrative function in Far Cry 3 and decode how the computer game with the help of certain binary opposition and codes have become one of the fundamental tools of getting entertained in the popular imagination.
Keywords: 1-Jeux vidéo; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Amérique du Nord (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

First-Person Encounters #4: Poornima Seetharaman - Game Studies India Adda (Game Studies India Adda, 2021)
First Person Encounters is a series of podcasts presented by Games Studies India, about our first experiences with Games while growing up in India. This our third podcast where we talk with Poornima Seetharaman. She is the first Indian to be inducted in the Women in Games (WIGJ) Hall of Fame and is also the lead game designer at Zynga. Hear as we talk about her foray in the world of gaming.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; 5-Créatrice; _Nettoyé

The Lure of Pokémon: Video Games and the Savage Mind - Nakazawa, Shin'ichi (Japan Publishing Industry Foundation for Culture, 2019)
From its humble beginnings as a video game launched in the mid-90s, Pokémon has become a global entertainment franchise, even reaching into the world via "augmented reality" with the mobile game Pokémon GO. In the work, Nakazawa Shinichi argues that the Pokémon worldview is the best contemporary example of Claude Lévi-Strauss's "savage mind" (la pensée sauvage), suggesting that computer games can often be viewed as attempts to reconnect the human unconscious with the true, hidden essence of nature.
Section: 1 v. (129 p.) : illustrations, couv. illustrations en coul. ; 22 cm
Keywords: 1-Jeux vidéo; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Video Games and Storytelling: Reading Games and Playing Books - Mukherjee, Souvik (Palgrave Macmillan, 2018)
The potential of video games as storytelling media and the deep involvement that players feel when they are part of the story needs to be analysed vis-a-vis other narrative media. This book underscores the importance of video games as narratives and offers a framework for analysing the many-ended stories that often redefine real and virtual lives.
OCLC: 1040048516
Keywords: 1-Jeux vidéo; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Playing with the Past: Digital Games and the Simulation of History - Kapell, Matthew Wilhelm; Elliott, Andrew B. R. (Bloomsbury Publishing USA, 2013)
Game Studies is a rapidly growing area of contemporary scholarship, yet volumes in the area have tended to focus on more general issues. With Playing with the Past, game studies is taken to the next level by offering a specific and detailed analysis of one area of digital game play – the representation of history. The collection focuses on the ways in which gamers engage with, play with, recreate, subvert, reverse and direct the historical past, and what effect this has on the ways in which we go about constructing the present or imagining a future. What can World War Two strategy games teach us about the reality of this complex and multifaceted period? Do the possibilities of playing with the past change the way we understand history? If we embody a colonialist's perspective to conquer 'primitive' tribes in Colonization, does this privilege a distinct way of viewing history as benevolent intervention over imperialist expansion? The fusion of these two fields allows the editors to pose new questions about the ways in which gamers interact with their game worlds. Drawing these threads together, the collection concludes by asking whether digital games - which represent history or historical change - alter the way we, today, understand history itself.
Google-Books-ID: jXjHAgAAQBAJ
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Beautiful Fighting Girl - Saitō, Tamaki; Azuma, Hiroki (University of Minnesota Press, 2011)
From Nausicaa to Sailor Moon, understanding girl heroines of manga and anime within otaku culture.
OCLC: 897044808
Keywords: 1-Cinéma; 1-Jeux vidéo; 1-TV; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma

Gaming Cultures and Place in Asia-Pacific - Hjorth, Larissa; Chan, Dean (Routledge, 2009)
This collection explores the relationship between digital gaming and its cultural context by focusing on the burgeoning Asia-Pacific region. Encompassing key locations for global gaming production and consumption such as Japan, China, and South Korea, as well as increasingly significant sites including Australia and Singapore, the region provides divergent examples of the role of gaming as a socio-cultural phenomenon. Drawing from micro ethnographic studies of specific games and gaming locales to macro political economy analyses of techno-nationalisms and trans-cultural flows, this collection provides an interdisciplinary model for thinking through the politics of gaming production, representation, and consumption in the region.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé